A Characterization of the Drivers, Pressures, Ecosystem Functions and Services of Namatala Wetland, Uganda - Namaalwa, S.; dam, A.A. Van; Funk, A.; Ajie, G.S.; Kaggwa, R.C. (Environmental Science & Policy, 2013)
Namatala wetland near the town of Mbale in the Eastern region of Uganda is a papyrus wetland that is subject to conversion for agriculture (mainly rice farming) and pollution by wastewater. The main goal of this study was to analyze the ecosystem functions and services of Namatala wetland and their drivers of change, and to suggest directions for sustainable use. Data on climate, hydrology, water quality, population and land use were collected. Stakeholder workshops were organized at national and local levels to identify stakeholder interests in the wetland and conflicts. The institutional context for management of Namatala wetland was analyzed. A qualitative assessment of the ecosystem services was performed. All results were integrated into a DPSIR network showing the drivers of change, impact on ecosystem services and possible responses for management. Results show that the communities around Namatala wetland strongly depend on the wetland ecosystem for provisioning services. A spatial gradient in ecosystem services was observed. The upper, converted part of the wetland is more important for provisioning services while the lower, more intact wetland supports regulating and habitat ecosystem services. The institutional framework is complex due to the involvement of several ministries at the national level and several levels of decentralized, local government. Horizontal and vertical coordination of policy implementation is weak. There are diverging perceptions among stakeholders about the priority issues in wetland management. Resource users worry about water and land use conflicts, while local and national government agencies are more concerned about agricultural encroachment and biodiversity loss. There are also differences in interpretation of land ownership between the national wetland policy and local customary arrangements. For sustainable management of Namatala wetland, there is a need for more horizontal and vertical coordination in wetland policy implementation, application of sustainable agriculture and integrated water and nutrient management techniques, and continued monitoring, research and capacity building to support adaptive management.
Keywords: Namatala wetland; Ecosystem services; Sustainable use of wetlands; Water quality; Wetland agriculture; Papyrus